2014
DOI: 10.1111/ejss.12186
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the water retention characteristics of UK mineral soils

Abstract: The management of water resources in compliance with regulatory requirements increasingly uses national environmental impact assessments incorporating models of soil solute transport. Most such models use either continuous functions designed to solve the Richards equation, or capacity-type functions based on water contents between specified soil water pressure heads. The work described here has used three separate sets of measured water-release data representative of the whole of the UK to develop a set of ped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 20 publications
(31 reference statements)
0
25
0
Order By: Relevance
“…In the three upland catchments moorland is the dominant land cover. The predicted saturated hydraulic conductivities ( K sat ) based on pedotransfer functions (Hollis et al ., ) range 33–235 mm h ‐1 with the highest K sat values in the Brotherswater and Loch of the Lowes catchments that contain the largest area of moorland. Notably, the range in K sat in the Loch of the Lowes catchment (66–202 mm h ‐1 ) is consistent with the reported range in mean K sat (56–224 mm h ‐1 ) for similar soils under woodland in the same region (Archer et al ., ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the three upland catchments moorland is the dominant land cover. The predicted saturated hydraulic conductivities ( K sat ) based on pedotransfer functions (Hollis et al ., ) range 33–235 mm h ‐1 with the highest K sat values in the Brotherswater and Loch of the Lowes catchments that contain the largest area of moorland. Notably, the range in K sat in the Loch of the Lowes catchment (66–202 mm h ‐1 ) is consistent with the reported range in mean K sat (56–224 mm h ‐1 ) for similar soils under woodland in the same region (Archer et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…Soil data for the catchments in England was supplied by the National Soil Resources Institute (NSRI, ) and by the James Hutton Institute for the catchments in Scotland (James Hutton Institute, ). Soil hydraulic parameters were estimated using pedotransfer functions based on soil texture (Hollis et al ., ). The soil parameters used in MMF‐TWI are summarized for each catchment in the Appendix (Table ).…”
Section: Model Simulationsmentioning
confidence: 99%
“…Five soil types were identified in the Blackwater catchment; the one with the largest extent (40%), namely, WICKHAM (Eutric Luvic Planosols), had a soil texture of 21% sand, 41% silt, and 30% clay. Each soil is characterized by five depth layers between 0 and 1.5 m; and the properties for each soil type and layer vary depending on the land use (Hollis et al, ). Six soil classifications with five depth layers (0–1.5 m) were identified in the Kit Brook catchment; BATCOMBE (18% sand, 58% silt, and 24% clay) and CHARITY (16% sand, 58% silt, and 26% clay) soils cover the 37% and 31% of the catchment, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Hollis et al, 2015) and (ii) the observed strength and nature (linear or quadratic) of the relations with FC and PWP (the Y variables) (Figures 2, 3) and the X variables (not shown). Bulk density and organic carbon content were included because of their importance and effect on water retention (Rawls et al, 2003;Hollis et al, 2015). Of the PSD fractions, clay and silt contents were included because they affect water retention (Hollis et al, 2015), and fine sand because it decreases water retention.…”
Section: Derivation Of Pedotransfer Functionsmentioning
confidence: 99%
“…Direct measurements of many soil properties, such as field capacity (FC) and permanent wilting point (PWP), are time consuming and expensive. Pedotransfer functions (PTFs) (Hollis et al , ) help to overcome these limitations through the derivation of an empirical predictive relation, in many cases regression based, of any such costly‐to‐measure soil property with other correlated soil properties that are more easily and economically measured. The data for derivation of these PTFs come from soil samples taken using various sampling designs that aim to identify the inherent spatial range and distribution of properties in a region.…”
Section: Introductionmentioning
confidence: 99%